Dwa paradygmaty samobójstwa czy dwa akty wolnej śmierci? Heinrich von Kleist i Jean Améry - Kuczyńska-Koschany, Katarzyna (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
I compare the suicide deaths of Heinrich von Kleist and Jean Améry (Hans Mayer). I discuss the issue of suicide, considering it as a category of the German language and distinguish the difference between the terms ‘Selbstmord’ [self-annihilation] and ‘Freitod’ [self-inflicted death, voluntary death]. By comparing the two suicides committed on the two verges of modernity (the beginning of 19th century in Berlin and 20th century after Auschwitz), I try to describe them as an experience of the imagination (in the words of Stefan Chwin) and as a specific act of creation: a choice of a voluntary death. Suicide, comprehended as a confirmation of our existential freedom, was a deviation from what was considered the norm in Prussia in 1811 and did not seem possible as anything else than an act of despair, when committed by a death camp survivor. However, Heinrich von Kleist and Jean Améry have set a precedent in the existing cultural and historical paradigms of suicide.
Two paradigms of suicide or two acts of voluntary death? Heinrich von Kleist and Jean Améry